Hedging and Speculative Trading in Agricultural Futures Markets. (8th January 2014) - Fishe, Raymond P. H.; Janzen, Joseph P.; Smith, Aaron
Abstract: Regulators and industry participants have expressed concern that excessive speculation harms agricultural futures markets. Such harm may arise if speculators cause prices to systematically differ from the price sequence that would arise in markets populated by equally informed traders with rational expectations (RE). We show theoretically that, when traders exhibit differences of opinion (DO) about the expected value of the commodity, futures prices may diverge from the RE equilibrium. Moreover, we develop a testable prediction, namely that positions held by different trader groups are correlated with prices in a DO equilibrium but not correlated in a RE equilibrium. We find strong empirical support for the DO-type environment; changes in positions held by managed money traders are positively correlated with prices, and changes in positions held by producers are negatively correlated. In the context of our DO model, this finding implies that prices change by more on average than producers think they should and by less than managed money thinks they should. However, the evidence suggests that neither group is systematically more prescient than the other.